2022
DOI: 10.1038/s41467-021-27794-4
|View full text |Cite
|
Sign up to set email alerts
|

Genomic alterations and evolution of cell clusters in metastatic invasive micropapillary carcinoma of the breast

Abstract: Invasive micropapillary carcinoma (IMPC) has very high rates of lymphovascular invasion and lymph node metastasis and has been reported in several organs. However, the genomic mechanisms underlying its metastasis are unclear. Here, we perform whole-genome sequencing of tumor cell clusters from primary IMPC and paired axillary lymph node metastases. Cell clusters in multiple lymph node foci arise from a single subclone of the primary tumor. We find evidence that the monoclonal metastatic ancestor in primary IMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…The intratumoral heterogeneity (ITH) patterns of the paired components in each sample were quantified to estimate the component’s genetic correlations. As expected, the MPP component had higher ITH levels compared with those of the non-MPP component, consistent with the aggressive profile of the MPP component, suggesting an expansionary predominance of this component in early progression [ 19 , 20 ] ( Figure 1 I), as reported previously [ 21 , 22 ]. These results suggest that, although there is some homology between MPP and non-MPP components, both emerged and retained their respective adaptive mutations during their development, with a more complex genomic landscape in the MPP region relative to the other components.…”
Section: Resultssupporting
confidence: 89%
“…The intratumoral heterogeneity (ITH) patterns of the paired components in each sample were quantified to estimate the component’s genetic correlations. As expected, the MPP component had higher ITH levels compared with those of the non-MPP component, consistent with the aggressive profile of the MPP component, suggesting an expansionary predominance of this component in early progression [ 19 , 20 ] ( Figure 1 I), as reported previously [ 21 , 22 ]. These results suggest that, although there is some homology between MPP and non-MPP components, both emerged and retained their respective adaptive mutations during their development, with a more complex genomic landscape in the MPP region relative to the other components.…”
Section: Resultssupporting
confidence: 89%
“…Caso et al ( 17 ) employed targeted next-generation sequencing (NGS), and revealed that tumors in the high-risk group had higher copy number amplifications, as well as statistical significance alteration in three oncogenic pathways (p53, Wnt, Myc), compared with those in the intermediate or low-risk group. Whole-genome sequencing of tumor cell clusters from MIP in breast cancer shares high-frequency copy-number loss of PRDM16 and IGSF9 and the copy-number gain of ALDH2 ( 18 ). In addition to the genomic instability, non-genetic factors also contributed to the functional and phenotypic heterogeneity of histological pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Screening for differentially expressed proteins in coronary artery disease congenital cold syndrome based on tandem mass-labeling techniques revealed upregulated expression of IGLV4-69 [42] . IGSF9 is active in axons and plasma membranes and plays a role upstream of dendrite development or in the regulation of dendrite organization [43] . IGSF9 was found to be associated with the prognosis of nasopharyngeal carcinoma and that downregulation of IGSF9 expression reduced the proliferation, migration and invasion of nasopharyngeal carcinoma cells, and that hypoxia induced IGSF9 expression [44,45] .…”
Section: Discussionmentioning
confidence: 99%